Modelo fenomenológico para a circulação de água na Bacia Sendimentar do Cariri com base em isótopos e hidroquímica - Silva, Carla Maria Salgado Vidal (1996)
The study area of this thesis in the Cariri region, in the south of Ceará State. It has the most important underground water resources of the State and comprises a plateau, the importance of the study is found in the fact irrigation, industrial and domestic water supply depend totally on these groundwaters. The main objective of this thesis is to study the dynamics of these waters with the help of environmental isotopes (carbon-14, carbon-13, oxygen-18, tritium, and teuterium), chemical analyses of the major ions, the electric conductivity and in the interpretation of geologic profiles. Through a synoptic vision of these data we design a conceptual hydrogeologic model for the underground waters of the Cariri. Waters from the Plateau discharges partly from springs at the interfaces of aquifer/aquiclude formations and in part percolate through the Santana Formation forming, that way, a contribution to the recharge of the Cariri Vallery aquifers. In the Vallery local recharge even of the deep aquifers can be identified in areas of strong tectonic features like the horst of Mauriti. Unconfined aquifers receive recharge mainly through alluvial deposits. Factorial statics confirm that the parameters taken as characteristic are well chosen.